2021
DOI: 10.18231/j.ijpo.2021.057
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological spectrum of enlarged lymph nodes

Abstract: Fine Needle Aspiration cytology (FNAC) is a simple, cost effective, rapid and reliable technique which can be used as a routine outpatient department (OPD) procedure and first line of investigation in diagnosing a variety of superficial and deep lesions. Enlarged lymph nodes is one of the common complaint in the surgical OPD's. Lymphadenopathy is of great clinical significance and the underlying cause may range from a treatable infectious etiology to malignant neoplasms. Any lymph node greater than 1 cm can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Most of the patients with reactive lymphadenitis were in the age group of 11 to 20 years. The study by Ashwini et al, [23] and Tiwari et al, [24] revealed that most patients with lymphadenopathy were cases of tuberculosis which is not consistent with the present study. The study conducted by Ashwini et al, [23] revealed that out of 310 lymph nodes 151 were tuberculosis, 109 were granulomatous and 15 were neoplastic (12 metastatic, 03 -Lymphoma).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…Most of the patients with reactive lymphadenitis were in the age group of 11 to 20 years. The study by Ashwini et al, [23] and Tiwari et al, [24] revealed that most patients with lymphadenopathy were cases of tuberculosis which is not consistent with the present study. The study conducted by Ashwini et al, [23] revealed that out of 310 lymph nodes 151 were tuberculosis, 109 were granulomatous and 15 were neoplastic (12 metastatic, 03 -Lymphoma).…”
Section: Discussioncontrasting
confidence: 92%
“…The study by Ashwini et al, [23] and Tiwari et al, [24] revealed that most patients with lymphadenopathy were cases of tuberculosis which is not consistent with the present study. The study conducted by Ashwini et al, [23] revealed that out of 310 lymph nodes 151 were tuberculosis, 109 were granulomatous and 15 were neoplastic (12 metastatic, 03 -Lymphoma). The study conducted by Attaullah et al, [25] found that of 235 cases of lymphadenopathy, 110 cases were of granulomatous lymphadenitis, which is in concordance with the present study.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation